Characterization of the novel mammarenavirus Sabiá-like (SABV-L) entry receptor and a potential therapeutic agent - Batto, María Victoria (2021)
Pathogenic Clade-B New World Mammrenaviruses (NWM) are the etiological agents of the South American Hemorrhagic Fevers, a family of priority-A pathogens due to their high infectivity and mortality, with of a patient, was identified in Brazil.